2012
DOI: 10.3109/13880209.2012.673627
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantiviral activity of Brazilian plants (Maytenus ilicifoliaandAniba rosaeodora) against bovine herpesvirus type 5 and avian metapneumovirus

Abstract: The biomonitored fractionation of the active extracts from M. ilicifolia and A. rosaeodora could be a potential tool for identifying their active compounds and determining the exact mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Among the species selected in this review, Anadenanthera colubrine (Vigerelli et al, 2014), Caesalpinia ferrea (Lopes et al, 2013; Marques et al, 2015), Lantana camara (Hasan, 2017), Maytenus ilicifolia (Khon et al, 2012), Schinus terebinthifolia (Nocchi et al, 2017), Solanum paniculatum (Valadares et al, 2009), Stryphnodendron adstringens (Felipe et al, 2006), Trichilia catigua (Espada et al, 2015) and Uncaria tomentosa (Caon et al, 2014; Reis et al, 2008) have already demonstrated action against different viruses which supports the antiviral potential of their constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Among the species selected in this review, Anadenanthera colubrine (Vigerelli et al, 2014), Caesalpinia ferrea (Lopes et al, 2013; Marques et al, 2015), Lantana camara (Hasan, 2017), Maytenus ilicifolia (Khon et al, 2012), Schinus terebinthifolia (Nocchi et al, 2017), Solanum paniculatum (Valadares et al, 2009), Stryphnodendron adstringens (Felipe et al, 2006), Trichilia catigua (Espada et al, 2015) and Uncaria tomentosa (Caon et al, 2014; Reis et al, 2008) have already demonstrated action against different viruses which supports the antiviral potential of their constituents.…”
Section: Resultsmentioning
confidence: 99%
“…The search for new therapeutic agents to control virus infection is one of the highest priorities in virological research [ 32 ], and an increasing number of recent studies have focused on utilizing natural sources to solve medical challenges [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aniba is a genus of plants native to the Brazilian Amazon. It comprises 41 species, including Aniba rosaeodora, which have been reported to have sedative, antiviral, anticonvulsant, and antidepressant activities [94,95]. A. rosaeodora has been reported to be highly effective against head lice [32].…”
Section: Anibamentioning
confidence: 99%